FEMINISME SEBAGAI KRITIK KAPITALISME: MEMPERKENALKAN TEORI KRITIS NANCY FRASER - Amin Mudzakkir (Institut Filsafat dan Teknologi Kreatif Ledalero, 2021)
This article is an overview of the intellectual and historical background of Nancy Fraser's thought. Intellectually, Fraser is a socialist feminist and critical theorist of the Frankfurt school who sought to reconnect gender analysis and the critique of capitalism. According to Fraser, the shift from state-managed-capitalism to neoliberal capitalism is the historical context that separates gender analysis and capitalism criticism in such a way that feminism is trapped as a handmaiden of neoliberalism. Based on an examination of Fraser's works and related literature, this article shows the problems of feminism in the neoliberal era and Fraser's critical theory offers to reclaim it.Key words: socialist feminism, critical theory, the Frankfurt School, gender, capitalism.